Short communication Anti-HCV antibodies detection frequency in groups of patients hospitalized on chosen clinical wards - Majek, Magdalena; Polański, Łukasz; Bełz, Mariusz (Archives of Medical Science, 2005)
After the outbreak of an endemy of hepatitis C, a number of epidemiological analyses have proven that the HCV infection poses a particular threat to patients and medical personnel. According to the latest statistic data, over 1.5% of Polish population are carriers of the pathogen. The route of HCV infection, which in 90% of cases transits from an acute to a chronic form, results in a major risk of late complications occurrence, including developing of hepatocarcinoma. Lack of effective specific treatment, places prophylaxis as the only way of preventing the disease. The following study was based on comparison between files from database from 1998 and experimental data from 2004. The experiment proved a substantial decrease in the number of positive results within the space of 6 years. Therefore the efficacy of unspecific prevention has been confirmed.